Environmental and economic impacts and trade-offs from simultaneous management of soil constraints, nitrogen and water. (10th June 2019) - Kodur, Shreevatsa; Shrestha, Uttam Babu; Maraseni, Tek Narayan; Deo, Ravinesh C.
Abstract: Nitrogen loss and soil salinity are two key global issues for sustainable farming systems. Simultaneous mitigation of these issues requires contrasting nitrogen and water management practices, warranting a holistic understanding of the resulting nitrogen losses. This research aims to understand the i) interactive effects of salinity management, soil conditions and rainfall variability on nitrogen leaching, and ii) general trends in economic and environmental trade-off from reduced leaching fraction and nitrogen applications to minimise nitrogen loss. Simulations were run for 116 years (1900–2015) taking irrigated Australian cotton as a reference. Results showed that nitrogen leaching increased with leaching fraction, from 1 to 4 kg ha −1 for a soil comprising of high plant available water capacity + low initial soil nitrogen to as high as 46 kg ha −1 for its counterpart condition. Leaching increased with in-crop rainfall, the wettest conditions (679 mm) contributing for, up to 75% additional leaching. Depending on soil salinity, trade-off involving leaching fraction reduction by 0.05 units (from typical 0.20) resulted in lower drainage (up to 6%) and lower leaching (up to 5%) but also reduced the net returns (up to 50%). In contrast, nitrogen fertiliser reduction by 25 kg ha −1 (from typical 250 kg ha −1 ) showed little benefit to leaching reduction, but led to lower economic losses, higher nitrogen use efficiency and lower nitrous oxide emission. The study suggests that nitrogen losses under salinity can be alleviated through avoiding over-irrigation but without compromising the critical leaching requirements, applying fertiliser according to the soil spatial variability, and maximising rainwater use to meet leaching needs. Highlights: Nitrogen leaching under salinity management was assessed. Leaching increased with leaching fraction, rainfall and soil nitrogen. Reducing leaching fraction proved costly than lowering nitrogen fertiliser. Precision farming and seasonal forecasting for rainwater use were promising.